The Impact of Human Capital Management and Resiliency on Employees Productivity - Askar, Nancy (International Journal of Economics, Business and Management Studies, 2020)
Human resources practices are considered one of the most important practices which should be practiced to maintain effective and efficient operations in the workplace. To increase the performance of alpha banks in Lebanon, Human Resources Development practices is the most important method that associations effort to retain the capability stages of their human resources. Since the Lebanese Banks in general and the Alpha banks in specific are facing a high employee turnover rate in the workplace because of absence of employee engagement practices and absence of talent management programs and human capital programs- the thing which demotivated employees and pushed them to search for a new job that best suits their needs and ambitions to develop their career. The Lebanese Banking Sector has been suffering recently from a fluctuation in its performance due to absence of efficient and effective human resources- practices in the workplace which resulted in a high turnover rate and by that affecting the overall productivity. The research will implement a mixed approach throughout distributing surveys over 370 participants in the Lebanese Alpha Banks, and through conducting in-depth interviews with managers in the Lebanese Alpha Banks. The research findings complied with the literature review findings and proved that the higher the empowerment, the higher the employees’ performance will be reflecting a higher productivity.